(untitled) (Al-Academy, 2016)
Represent the current study and tagged (the credibility of digital image and its reflection on the process of cognitive picture releases) scientific effort is designed to detect realizing press releases and the extent affected the credibility of the digital image by selecting the relationship between digital photo and the extent of their credibility on the one hand and between the process of cognition and Press Photo of the hand Other than the consequent establishment researcher collects materials to serve the scientific research topic in three chaptersCombine the first one methodological framework for the search of the research problem and its significance and the desired objective be achieved together with the definition of the most important terms contained in the title search also included the separation mechanism followed by the researcher to achieve the goal by monitoring the impact digital photo on the credibility of the process of realization of the image press according to the researcher survey based on observation and analysisChapter II included on the theoretical Stases the framework of the way to achieve the target and thus monitor the effects on the picture releasesChapter III included the conclusions of the researcher during his analytical and the overall focus on the fact that the growing phenomenon of digital picture and increased awareness as a means connectivity distinct its technologies and their implications and impact and vocabulary own and despite the many advantages added by Technology digital communication in the field of image processing, but it created a lot of ethical practices unacceptable on the one hand and controversial on the other handThe study also reveals the occurrence of some of the renowned media institutions into the trap of digital image manipulation and thus a lot of mistakes moral in this area